Arthroscopic Transosseous-Equivalent Double-Row Rotator Cuff Repair Augmentation With Interpositional Demineralized Bone Fiber Implant - Juan Bernardo Villarreal-Espinosa, M.D.; Rodrigo Saad-Berreta, B.A.; Richard Danilkowicz, M.D.; Zeeshan A. Khan, B.A.; Stephanie Boden, M.D.; Nikhil N. Verma, M.D. (Arthroscopy Techniques)
Failure of rotator cuff repairs contributes to decreased patient satisfaction and quality of life. Biologic enhancement of repairs represents a novel augmentation strategy attempting to reproduce native healing while concomitantly potentially decreasing the existing high failure rates associated with rotator cuff repairs. Scaffolds placed on top of the rotator cuff have been widely studied, yet no recreation of the native enthesis is achieved via this augmentation strategy. Several strategies involving placement of demineralized bone matrix scaffolds on an inlay configuration (between bone and tendon) have been reported demonstrating enhanced recreation of the native bone-tendon unit. This Technical Note describes the surgical technique of inlay demineralized bone fiber scaffold augmentation of rotator cuff repairs to enhance biological healing in aims of recreating the native enthesis.